The Snow Must Go On! A Way, Way Off-Broadway Adventure - Wigand, Molly; Esberg, Mike ([United States] : Hallmark, 2006)
On Christmas Eve residents of Antarctic Springs put on a big show to tell everyone that the South Pole is a jolly place to be at Christmastime.
Keywords: Penguins -- Juvenile fiction; Christmas -- Juvenile fiction; Antarctica -- Juvenile fiction; Christmas stories -- Juvenile fiction